Fever of Unknown Origin in Children - Hossain, Mahmud (Journal of Monno Medical College, 2024)
Fever is a common symptom in children and fever of unknown origin (FUO) is not uncommon in paediatric age group. The FUO remains a challenging clinical problem and is an important cause of morbidity and mortality in children. These undifferentiated prolonged fevers need step-wise approach for diagnosis. Details and proper history taking, thorough serial physical examination, critical analysis of sign-symptoms diary and investigation reports are crucial to get a clue that led to the diagnosis. Though in some aspect more concerned with developing countries data, this article is based on reviewing of published papers from both developed and developing countries. Worldwide infection remains the most common cause of FUO in children, followed by collagen vascular diseases, neoplasm, miscellaneous diseases and undiagnosed illnesses. Indiscriminate use of antimicrobials and other medications may mask the real diagnosis. Awareness of primary-level healthcare providers about the cause and logical management approach of pediatric FUO is important for better outcome. Journal of Monno Medical College December, 2023; 9 (2):78-84